Wieczorne oświetlenie kopuły kościoła Mądrości Bożej w Konstantynopolu: rekonstrukcja systemu oświetleniowego za Pawłem Silencjariuszem ("Descriptio Sanctae Sophiae", 806–835) - Garnczarska, Magdalena (Vox Patrum, 2026)
Lighting was one of the most vital aspects of everyday life in the Byzantine Empire. This problem also affected churches. This was even more so when one considers that a dark church was deemed unsuitable for worship – the house of God should be well illuminated. For example, Procopius of Caesarea made this clear when he explained why Emperor Justinian I had to rebuild so many temples. The most prominent church in the empire had to serve as a model in all aspects. There is no shortage of written (or artistic) sources on the issue of the lighting of this church. Among them, verses 806-835 from the “Ekphrasis of the Divine Wisdom Church” (Ἔκφρασις τοῦ ναοῦ τῆς ἁγίας Σοφίας) by Paul the Silentiary hold a special place. In this article, I assume that light in Byzantine culture was not only a practical necessity but also a theological and aesthetic medium of divine manifestation, and that Paul’s ekphrasis combines poetic erudition with an extraordinary precision of description, rarely found in such texts. The aim is to examine this fragment in detail to reconstruct the evening lighting system of Hagia Sophia’s dome in Justinian’s time and to explore its symbolic and artistic significance. By doing so, the study demonstrates how a literary source can provide both insight into architectural solutions and evidence of the ideological message conveyed by the illuminated sacred space.